Participatory monitoring in tropical forest management: a review of tools, concepts and lessons - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
A resource book that includes concepts and terms in participatory monitoring; synthesis of the lessons learned, organized along two broad themes: planning and implementing participatory monitoring and the main impacts of participatory monitoring; and a table of publications organized by theme: forest management for various objectives, biodiversity conservation and wildlife management, human wellbeing, political processes and institutions, non-timber forest products and ecosystem services. It provides a quick reference guide to specific aspects of participatory monitoring, such as tools, methods and monitoring topics.